KEBERADAAN SOLUSI PERSAMAAN DIOPHANTIN MATRIKS POLINOMIAL DAN PENYELESAIANNYA MENGGUNAKAN TITIK-TITIK INTERPOLASI - Istiani, Laila; Utomo, Robertus Heri (MATEMATIKA, 2008)
Diophantine equation is a matrix polynomial equation of the form . Here, we investigate the existence of the solutions . It can be investigated by using the grestest common right divisors of the matrix . Then, the solutions can be solved by transforming to the form of the polynomial matrix equation . By taking the interpolation points will be obtained the solutions Â of degree r. Â